UNDERWATER OBSERVATION OF SUBLITTORAL OF THE BARENTS SEA (Podvodnye Nablyudeniya v Sublitorali Barentseva Morya) - Propp,M. V. (1964)
The findings of underwater investigations carried out in the Murman sublittoral of the Barents Sea are outlined. The applications and advantages of various types of diving suits for summer and winter seasons are pointed out. Also the use of still and motion picture cameras and the significance of the photographs in determining the littoral fauna and flora and their migrations are discussed. The investigations disclose the presence in the littoral of many warm-water species that have been brought by the Nordkapp current. (Author) Trans. of Akademiya Nauk SSSR. Okeanograficheskaya Komissiya. Trudy, v14 p73-75 1962, by M. Slessers. Also available as TT-64-19535.